2021
DOI: 10.1038/s41598-021-82241-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of kinesthetic motor imagery compared with visual motor imageries

Abstract: Motor imagery (MI) is the only way for disabled subjects to robustly use a robot arm with a brain-machine interface. There are two main types of MI. Kinesthetic motor imagery (KMI) is proprioceptive (OR somato-) sensory imagination and Visual motor imagery (VMI) represents a visualization of the corresponding movement incorporating the visual network. Because these imagery tactics may use different networks, we hypothesized that the connectivity measures could characterize the two imageries better than the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…In a similar vein, that CSE facilitation during dynamic kMI is affected by S1 rTMS is in keeping with neuroimaging studies showing the involvement of S1 activation, in particular during kMI [25,29,30]. Remarkably, our findings support the notion that connectivity between S1 and M1 during MI may be inhibitory [24], since we found that transient suppression of S1 boosts the facilitation of CSE during kMI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a similar vein, that CSE facilitation during dynamic kMI is affected by S1 rTMS is in keeping with neuroimaging studies showing the involvement of S1 activation, in particular during kMI [25,29,30]. Remarkably, our findings support the notion that connectivity between S1 and M1 during MI may be inhibitory [24], since we found that transient suppression of S1 boosts the facilitation of CSE during kMI.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of decreased muscle-specific facilitation of CSE during kMI following rTMS over the dPMC falls in line with previous evidence of strong activity of this area during kMI [25,26,29,30]. The dPMC activation during kMI was linked to an increase in the MEP amplitude of hand muscles following spTMS over the relative OSP [69].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We designed a task paradigm similar to that in our previous paper 32 . We used a block design because movement imagery is di cult without any preceding practical task 21 .…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, the participant further received passive movements using the pedal to feel the kinesthetic experience, to afterward imagine the same kinesthetic experience [44,45]. Kinesthetic motor imagery is described as the ability to imagine the execution of a movement by having an impression of muscle contraction and sensation during a real movement [46,47]. Simultaneously, the skin preparation and placement of EEG electrodes were done while the participant was instructed to continue training the kinesthetic motor imagery, following the visual cues (see Figure 1) provided by the BCI.…”
Section: Protocolmentioning
confidence: 99%